Tunable active grounded lossless and lossy inductance simulators with single grounded capacitor using VDBAs - Tangsrirat, W.; Surakampontorn, W. (My University, 2022)
This study presents three active-C synthetic grounded inductance simulator circuits that realize tunable lossless and lossy series and parallel R-L type inductances. Each of these circuits employs two Voltage Differencing Buffered Amplifiers (VDBAs) as active components and a single grounded capacitor as a passive component. In all the proposed circuits, the simulated equivalent resistance and inductance values can be adjusted electronically through the transconductance gains of the VDBAs. They also do not require any critical component matching conditions and cancellation constraints. Details of non-ideal analysis including transfer errors of the VDBA has been analyzed. For circuit performance verification and comparison, some application examples are given together with computer simulation results by PSPICE program.
Keywords: Electronically tunable circuit; Grounded inductance simulator; Lossless inductor; Lossy inductor; Voltage Differencing Buffered Amplifier (VDBA)